1989
DOI: 10.1203/00006450-198903000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Breathing Cycle Duration in Preterm Infants

Abstract: ABSTRACT. Periodic breathing cycle duration (PCD),PB, a respiratory pattern consisting of alternating respiratory pauses and breaths, has been studied extensively in infants during the last decade. PB comprises <2% of the respiratory pattern in most normal infants during the first months of life (1-3), and occurs more frequently and in higher amounts in preterm infants (4-8). PB may therefore reflect an immaturity of developing respiratory control system elements which does not normally indicate any abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
8
3
Order By: Relevance
“…These findings are similar to those we (8,9) and others (7) have previously reported in term infants. Our data showing the decrease in PCD with maturation in preterm infants are clearly at variance with the study of Glotzbach et al (15) which showed no significant change in PCD with postnatal age in a group of 51 preterm infants. However, there are several methodologic differences between the two studies that might explain the discrepancies between them.…”
Section: Discussioncontrasting
confidence: 57%
“…These findings are similar to those we (8,9) and others (7) have previously reported in term infants. Our data showing the decrease in PCD with maturation in preterm infants are clearly at variance with the study of Glotzbach et al (15) which showed no significant change in PCD with postnatal age in a group of 51 preterm infants. However, there are several methodologic differences between the two studies that might explain the discrepancies between them.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast to the situation in term infants, data on PCD maturation in preterm infants are contradictory. The current study and our earlier work (1) demonstrate PCD falls with PNA, whereas a study by Glotzbach et al (8) reported no change in PCD with PNA. The possible reasons for this discrepancy have been discussed in some detail previously (1).…”
Section: Discussioncontrasting
confidence: 54%
“…Also plotted in Figure 2, c and d, are published PCD data from previous studies. Note in Figure 2, c that the data of Glotzbach et al (8) show a rising trend with PNA, whereas our previous (1) and current data demonstrate a progressive fall in PCD with maturation; the single point is from Rigatto et al (13). All three existing studies in term infants (5-7) show a fall in PCD with PNA and are in good agreement with the regression curve derived from our current data (Fig.…”
Section: Resultscontrasting
confidence: 39%
See 1 more Smart Citation
“…This accounts for variability in the PB cycle duration from 10–40 seconds. PB is usually seen in the 10–20 second range (Barrington, Finer & Wilkinson 1987, Wilkinson et al 2007, Glotzbach et al 1989), but PB has been defined as having breathing segments of up to 20 seconds duration (Barrington, Finer 1990). PB was analyzed for each infant during the entire NICU stay by shifting the family of wavelets along the apnea signal at quarter second intervals (Figure 3a–b).…”
Section: Methodsmentioning
confidence: 99%